Neuromuscular adaptations to short-term high-intensity interval training in female ice-hockey players - Kinnunen, J.-V.; Piitulainen, H.; Piirainen, J. M. (The Journal of Strength and Conditioning Research, 2019)
High-intensity interval training (HIIT)-related neuromuscular adaptations, changes in force production, and on-ice performance were investigated in female ice-hockey players during preseason. Fourteen Finnish championship level ice-hockey players (average age 22 ± 3 years) participated in 2½-week HIIT. Both spinal (H-reflex) and supraspinal (V-wave) neuromuscular responses of the soleus muscle were recorded before and after the training period. Static jump (SJ) and countermovement jump heights, plantarflexor maximum voluntary contraction (MVC), and rate of force development (RFD) were measured. In addition, soleus and tibialis anterior muscle activations (electromyography) were measured during MVC and RFD tests. During on-ice training, skating speed and acceleration tests were performed. Subjects significantly improved their plantarflexion MVC force (11.6 ± 11.2%, p < 0.001), RFD (15.2 ± 15.9%, p < 0.01), and SJ (4.8 ± 7.6%, p = 0.05). Voluntary motor drive to the soleus muscle (V-wave amplitude) increased by 16.0 ± 15.4% (p < 0.01), and coactivation of the tibialis anterior muscle during the plantarflexion RFD test was reduced by -18.9 ± 22.2% (p = 0.05). No change was observed in spinal a-motoneuron excitability (H-reflex) during MVC or in on-ice performance. These results indicate that HIIT can be used to improve athletes' capability to produce maximal and explosive forces, likely through enhanced voluntary activation of their muscles and reduced antagonist coactivation. Therefore, HIIT can be recommended in preseason training to improve neuromuscular performance. However, a longer than 2½-week HIIT period is needed to improve on-ice performance in female ice-hockey players.